Evaluation of noscapine-licorice combination effects on cough relieving in COVID-19 outpatients: A randomized controlled trial - Barati, Saghar; Feizabadi, Faezeh; Khalaj, Hakimeh; Sheikhzadeh, Hakimeh; Jamaati, Hamid R.; Farajidavar, Hirad; Dastan, Farzaneh (Frontiers in Pharmacology, 2023)
Background: As February 2023, SARS-CoV-2 is still infecting people and children worldwide. Cough and dyspnea are annoying symptoms almost present in a large proportion of COVID-19 outpatients, and the duration of these symptoms might be long enough to affect the patients’ quality of life. Studies have shown positive effects for noscapine plus licorice in the previous COVID-19 trials. This study aimed to assess the effects of the combination of noscapine and licorice-for relieving cough in outpatients with COVID-19. Methods: This randomized controlled trial was conducted on 124 patients at the Dr. Masih Daneshvari Hospital. Participants over 18 years of age with confirmed COVID-19 and cough were allowed to enter the study if the onset of symptoms was less than 5 days. The primary outcome was to assess the response to treatment over 5 days using the visual analogue scale. Secondary outcomes included the assessment of cough severity after 5 days using Cough Symptom Score, as well as the cough-related quality of life and dyspnea relieving. Patients in the noscapine plus licorice group received Noscough® syrup 20 mL every 6 h for 5 days. The control group received diphenhydramine elixir 7 mL every 8 h. Results: By day five, 53 (85.48%) patients in the Noscough® group and 49 (79.03%) patients in the diphenhydramine group had response to treatment. This difference was not statistically significant (p-value = 0.34). The presence of dyspnea was significantly lower in the Noscough® group versus diphenhydramine at day five (1.61% in the Noscough® group vs. 12.9% in the diphenhydramine group; p-value = 0.03). The cough-related quality of life and severity also significantly favored Noscough® syrup (p-values <0.001). Conclusion: Noscapine plus licorice syrup was slightly superior to diphenhydramine in relieving cough symptoms and dyspnea in the COVID-19 outpatients. The severity of cough and cough-related quality of life were also significantly better in the noscapine plus licorice syrup. Noscapine plus licorice may be a valuable treatment in relieving cough in COVID-19 outpatients.